Monitoring The Physical Performance Of Volleyball Players - Kazakov Allayar Radjapovich (Zien Journals, 2024)
This article discusses the physical fitness of athletes (volleyball players), the types and methods of training, and the control over the physical performance of volleyball players.
Keywords: Volleyball; tests; athletes